Polishing force control strategy for pneumatic end-effector based on adaptive fuzzy algorithm with state observer - Yang, Zhiguo; Zhao, Wenbo; Kou, Jiange; Ma, Yushan; Wang, Yixuan; Li, Zhanxin; Shi, Yan (International journal of advanced manufacturing technology, 2025)
This paper investigates force tracking control for pneumatic polishing end-effector under model uncertainty and unmeasured states. A fuzzy logic system approximates unknown nonlinear characteristics, while a fuzzy state observer estimates unmeasured states. Based on these estimates, an adaptive output feedback controller is developed by integrating dynamic surface control with an adaptive backstepping strategy. This approach reduces computational burden and avoids the issue of derivative explosion. A barrier Lyapunov function is introduced to implement output constraints, and finite-time boundedness is proven for all closed-loop signals. Pneumatic polishing force control experiments are conducted under three typical operating conditions—constant force, sinusoidal force, and time-varying amplitude/frequency—validating that the proposed method significantly improves force tracking accuracy, accelerates response speed, and reduces overshoot compared to PID controllers and two state-of-the-art benchmark schemes. This fully demonstrates the effectiveness of the proposed approach.